IDENTIFICATION OF FUNGAL INFECTION IN KISSING GOURAMI (Helostoma temminckii) CULTURED IN SERUYAN REGENCY, CENTRAL KALIMANTAN, INDONESIA - Bagus Ansani Takwin; Mazlan Mazlan; Gabriella Augustine Suleman; Yunarty Yunarty; Ardana Kurniaji (Politeknik Kelautan dan Perikanan Bone, 2026)
The kissing gourami (Helostoma temminckii) is an economically valuable freshwater fish species with increasing potential for aquaculture development. However, fungal infection remains an important health problem in its culture system. This study aimed to identify the fungal agent infecting cultured kissing gourami and to determine the prevalence and intensity of infection in aquaculture ponds in Seruyan Regency, Central Kalimantan, Indonesia. The study was conducted for 30 days, with fish sampling performed every five days across six observation periods. Fungal examination used mucus samples collected from the body surface, fins, and gills. The fungal agent was identified based on macroscopic and microscopic characteristics. The results showed that the fungal agent identified in infected kissing gourami was Saprolegnia sp. The prevalence of infection ranged from 0.7–6.0% , based on 150 fish examined during each sampling period. The lowest prevalence occurred on day 10, while the highest prevalence occurred on day 30. The intensity of infection ranged from 2–7 colonies/fish, indicating very low to low infection intensity. Microscopically, Saprolegnia sp. was characterized by long, branched, aseptate hyphae. Clinically, infected fish showed cotton-like white patches, fin erosion, and ulcerative lesions on the body surface. These findings indicate that Saprolegnia sp. is an opportunistic fungal pathogen in cultured kissing gourami. Therefore, routine fish health monitoring and proper water quality management are essential to minimize the risk of saprolegniasis in aquaculture ponds.